Growth of Population Density -2020-2021 Thanjavur Districts, Tamilnadu. To Using the Geographical Information System - and R. Baskaran, T. Sangeetha* (Recent Research in Science and Technology, 2010)
Abstract In this study I have used a population project model to estimate the population growth for Thanjavur district, Tamil nadu. Until the years 2021 and to calculate the current and future needs elements in urban planning of the Thanjavur district. For urbanizations, I have employed GIS arc Info to digitize the maps and GIS-arc view to process the data combining with other analytical measurements to display the result. Keywords: Population analysis Thanjavur district, Geographical information system, Statistical forecasting method